A RARE CASE OF NON-CLASSICAL TYPE OF CONGENITAL ADRENAL HYPERPLASIA IN A 27-YEAR-OLD FEMALE - Ali, Masab; Ahmad, Muhammad Husnain; Mirza, Zaid Ashraf (Journal of Ayub Medical College Abbottabad, 2024)
This case report presents the case of a 27-year-old female patient with a complex clinical presentation, diagnosed with nonclassical congenital adrenal hyperplasia (NCCAH). The patient presented with a constellation of symptoms including hirsutism, acne, hyperpigmentation, amenorrhea, frontal baldness, and renal stones, posing diagnostic challenges. Comprehensive evaluation revealed NCCAH, emphasizing the importance of considering this condition in cases of hyperandrogenism. Treatment with oral dexamethasone and oral contraceptive pills resulted in gradual symptom improvement. This case underscores the necessity for thorough clinical assessment and awareness of NCCAH as a differential diagnosis in patients with hyperandrogenic symptoms.